Custodian of the Family Home - Mumbai Archive Project Team (Jio Institute, 2024)
As the eldest surviving member of the family, Saraswati Nakhva serves as the custodian of the family home. She resides there with her sister-in-law, Meena Nakhwa, diligently maintaining the house her father had built with love and dedication.